Adopting lean manufacturing techniques in small and medium manufacturing enterprises - Danielli, Shaun Pau (Cranfield University, 2010)
Small and medium sized enterprises (SMEs) form a significant part of national and regional economic prosperity. They strengthen the capacity to generate employment and wealth for national and regional benefit. The importance of SMEs to the prosperity of a society and their contribution to new job creation, coupled with the recognition that they seem to underperform highlights the need to assist this group of companies improve their performance. During the course of this research the author investigated whether SME manufacturing organisations had opportunities to improve productivity and performance, conducted a literature review of the application of cellular one piece flow and then tested a model to implement cellular one piece flow with three SME manufacturing organisations. This thesis establishes that SME manufacturing organisations do have opportunities to improve productivity and performance through cellular one piece flow.